The effect of menses on standardized assessment of sexual dysfunction among women with uterine fibroids: a cohort study - Laughlin-Tommaso, Shannon K. (Fertil Steril, 2015)
OBJECTIVE: To determine if assessment of sexual dysfunction by the Female Sexual Function Index (FSFI) is related to whether the FSFI is administered during or between menses in women with symptomatic uterine fibroids DESIGN: Prospective cohort SETTING: US academic medical centers PATIENTS: Premenopausal women with symptomatic uterine fibroids enrolled in fibroid treatment trials INTERVENTIONS: FSFI administered during and between menses MAIN OUTCOME MEASURES: FSFI mean scores in each of 6 domains and a discordance score to report individual differences in assessment RESULTS: Thirty-three women completed the FSFI during menstruation and at a time in their cycle when they were not menstruating. The mean FSFI scores for each domain did not differ based on when in the menstrual cycle the instrument was administered. However, on an individual level, nearly half of the women reported sexual dysfunction differently during menses than between menses. Of those that differed, pain and desire domains improved; lubrication, and satisfaction worsened during menses. CONCLUSIONS: Although the mean values of the domain scores were not different, women did report differences in sexual functioning between menses and non-menses reporting. Timing of the questionnaire in relation to menses should be considered in sexual dysfunction assessment for women with uterine fibroids.